As metamorfoses da escrita gótica em Wuthering Heigths (O Morro dos Ventos Uivantes) - Alegrette, Alessandro Yuri [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
O corpus deste trabalho de pesquisa é O Morro dos Ventos Uivantes, único romance da autora inglesa Emily Brontë que desde de sua primeira publicação em 1847 tem gerado reações contraditórias que oscilam entre o fascínio e o estranhamento entre os leitores. Buscamos analisar alguns aspectos peculiares dessa obra, enfatizando-se dentre eles seu modo de narração, que combina aspectos assustadores do romance gótico com elementos da estética realista do século XIX. Também são objetos de estudo desta pesquisa o que chamamos de “espacialidade gótica”, que se evidencia nas descrições do cenário principal - Wuthering Heights, a antiga e sinistra casa que também dá o título ao romance -, e os temas e motivos do gênero gótico que foram revistos por Emily Brontë, tais como o duplo, o qual é amplamente explorado em textos com inspiração gótica, a exemplo de Manfred, poema dramático de Byron. Por fim, realizamos a análise das características do casal de protagonistas do romance, Catherine e Heathcliff, visando apontar um diálogo intertextual do livro de Brontë com obras do gênero gótico ou inseridas na tradição literária inglesa, tais como Paraíso perdido, de John Milton.

The corpus of this research is Wuthering Heights, the only novel written by the English writer Emily Brontë that since its first publication in 1847 has generated contradictory reactions that oscillate between fascination and repulsion among readers. We analyse some peculiar aspects of this work, emphasizing among them, its mode of narration that combines frightening aspects of Gothic novel with elements of realistic aesthetics of the nineteenth century. They are also objects of this study, which we call "Gothic spatiality" that stands out in the description of its main scenario - Wuthering Heights, the old and sinister house that provides the title of the novel -, and the themes and motifs of the Gothic genre that were reviewed by Emily Brontë, such as the double, which is widely exploited in texts with Gothic inspiration, such as Manfred, dramatic poem of Byron. Finally we analyse the couple of protagonists in the novel, Catherine and Heathcliff, seeking to appoint an intertextual dialogue between Brontë’s book with works of Gothic genre or inserted in the English literary tradition, such as Paradise Lost, by John Milton.
The metamorphoses of Gothic writing in Wuthering Heights
Keywords: O Morro dos Ventos Uivantes; Romance gótico; Espaço; Heathcliff; Intertextualidade; Wuthering Heights; Gothic novel; Space; Intertextuality